2017
DOI: 10.1155/2017/1414070
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Promotes CD36 Expression by Upregulating Peroxisome Proliferator-Activated Receptor γ Levels to Exacerbate Lipid Deposition in Renal Tubular Cells

Abstract: Diabetic kidney disease (DKD) appears to be closely related to lipid deposition in kidney. The aim of this study was to determine whether high glucose (HG) exacerbated lipid deposition by increasing CD36 expression via AKT-PPARγ signaling pathway. Our results showed that HG activated AKT signaling pathway, followed by an increase in PPARγ that induced CD36 overexpression, ultimately causing lipid deposition in HK-2 cells. We also found that inhibition of AKT-PPARγ signaling pathway or knockdown of CD36 could r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…In addition, study have shown that PPARγ dependent pathway increase CD36 expression can be activated by high glucose in the human HK-2 proximal tubular cell line. 46,47 Whether or not the CD36 promoter contains a PPAR responsive element, however, remains unclear. Response element binding sites for Pregnane X receptor (PXR) and liver X receptor (LXR) have been identified in the CD36 promoter, and activation these receptors could upregulate CD36 expression and promote hepatic steatosis .…”
Section: [H2] Transcriptional Regulationmentioning
confidence: 99%
“…In addition, study have shown that PPARγ dependent pathway increase CD36 expression can be activated by high glucose in the human HK-2 proximal tubular cell line. 46,47 Whether or not the CD36 promoter contains a PPAR responsive element, however, remains unclear. Response element binding sites for Pregnane X receptor (PXR) and liver X receptor (LXR) have been identified in the CD36 promoter, and activation these receptors could upregulate CD36 expression and promote hepatic steatosis .…”
Section: [H2] Transcriptional Regulationmentioning
confidence: 99%
“…8 It is known that abnormal glucose metabolism affects lipid homeostasis by regulating the expression of genes related to lipid metabolism, 9 and multiple enzymes, carrier proteins, and lipoprotein receptors, such as 3-hydroxy-3methylglutaryl-CoA reductase (HMGCR), sterol regulatory element-binding protein-2, sterol regulatory elementbinding protein cleavage-activating protein, CD36, and low-density lipoprotein receptor, have been found to participate in lipid droplet (LD) deposition in the kidney by increasing cholesterol uptake and synthesis. 10,11 However, other mechanisms involved in renal EFD and lipidrelated kidney damage need to be identified.…”
mentioning
confidence: 99%
“…An increasing number of studies have linked the activation of sterol regulatory element-binding proteins (SREBPs), the dysfunction of peroxisome proliferator-activated receptors (PPARs), and inhibited -oxidation of fatty acids with diabetic nephropathy [9]. High glucose may initiate lipid deposition on renal tubular cells by upregulating CD36 and PPARs [10]. SREBP-1c, regulated by the insulin and AMPK signaling pathways, was found to play a role in nonalcoholic fatty liver disease [11].…”
Section: Introductionmentioning
confidence: 99%